Group theory selected problems - Sury B (Hyderabad Universities Press, 2004)
The problems which have included, are not found in standard texts of Artin, Fraleigh, Herstein, Hungerford & Lang. These problems are meant only to supplement the existing ones in them & not to substitute for them. The author has derived from two textboo
Keywords: Group theory; Problems and exercises